Vegetation and habitat structure that determines the diet of insectivorous birds in agroforestry systems - García-Núñez, Rosa María; Romero-Díaz, Claudio; Ugalde-Lezama, Saúl; Tinoco-Rueda, Juan Ángel (Revista Mexicana de Ciencias Agrícolas, 2020)
To define the vegetation and habitat structure in relation to the presence of birds and prey from August (2018) to January (2019), the monitoring of birds, vegetation and insects was carried out, using counting at points with a fixed radius; intensive search; cut and shake of branches, Canfield lines, quadrants with center point and closest neighbor. Observation frequency (FO) and relative abundance index (IAR) were determined. Kruskal wallis and X2 analyzes were carried out to determine differences and determine if what was recorded is expected. To assess association between habitat and vegetation in relation to the presence of birds and insects, a Poisson regression analysis (ARP) was applied. To know the degree of inertia between habitat and vegetation in response to the presence of birds and insects, canonical correspondence analysis (ACC) was developed. The FO indicates high values for: Birds Melanerpes aurifrons, Cyanocorax morio and Empidonax sp.; Poaceae, Selaginellaceae and Verbenaceae vegetation; insects Plecia nearctica and Chauliognathus pensylvanicus. The IAR indicates high values for: Poaceae, Selaginellaceae and Verbenaceae vegetation; insects Plecia nearctica and Chauliognathus pensylvanicus. Kruskal wallis without differences and X2 that what is registered is expected. The ARP suggests an AIC= 283.65; 219.4; 240.38. The ACC shows an inertia of 66.26%; 78.54%; 93.89% and 84.62%. Vegetation and habitat structure are determining factors in the abundance of birds, they have a food stock that guarantees the conservation and ecological balance of agroforestry systems.
Keywords: birdlife; conservation; feeding; tree cover; systematic sampling